PERBEDAAN KAPASITAS KERJA FISIK PEKERJA NON PRODUKSI, WEAVING, DAN SPINNING PABRIK TEKSTIL BANDUNG - Putri Teesa Radhiyanti; Ieva Baniasih Akbar; Juliati Juliati; Reni Farenia; Ambrosius Purba (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2018)
Workers of PT. Grandtex is divided into three different divisions; nonproduction division, weaving division, and spinning division. These workers have different activities, job processes, and work environments, especially in the cotton dust exposure rate. Exposure to cotton dust can influence physical working capacity. This study aimed to find out physical working capacity differences between workers of nonproduction division, weaving division, and spinning division. A comparative analytic survey study is conducted on 112 subjects, which consists of 32 nonproduction division workers, 40 weaving division workers, and 40 spinning division workers. Subjects are picked by the stratified random sampling method. Physical working capacity measured by using an anaerobic capacity parameter (V̇O2 max)with the Astrand-Rhyming chair test. The homogeneity of the result is tested by the Levene test and the normality is tested by Kolmogorov-Smirnov. To find out the differences, those data are analyzed by one-way ANOVA test (p<0,05) and followed by Duncan test to measure how big the differences are. The result of data analyzed with ANOVA indicated that there is a significant difference in physical working capacity (V̇O2 max)(p=0,000) among workers of nonproduction, weaving, and spinning division. This result was also followed by Duncan’s test suggesting thatthe physical working capacity (V̇O2 max) of nonproduction workers are bigger than weaving production workers and also bigger than spinning workers (35,78 ± 7,27 vs 31,50 ± 7,59 vs 28,03 ± 5,92 ml/kg BW/minute). From this study, we can conclude that the physical working capacity (V̇O2 max) of nonproduction workers is better than weaving and spinning division workers.